Three-phase permanent magnet synchronous motor speed control using pulse width modulation technique / Mohd Zekeryllah Abdullah - Abdullah, Mohd Zekeryllah (2010)
Three-phase permanent magnet motor has some performance advantages over induction motor and has become predominant in fractional horsepower applications. They are more efficient and reliable. However, users need to control the speed of the motor depending on the desired speed and application. So, this project presents the three phase permanent magnet synchronous motor speed control by varying the electrical frequency. In this project, the frequency is adjusted by using insulated gate bipolar transistor (IGBT) and pulse width modulation (PWM) technique based on Matlab simulation as a variable frequency drive. The speed of permanent magnet motor will depends on the rate of rotation of its magnetic field. So, the objective is to study the general characteristic of the three-phase permanent magnet motor and the speed control technique by using IGBTs and PWM. Simulation results are presented, with design PWM control algorithm for switching of IGBTs to control the speed of permanent magnet motor. The simulation results were carried out using Matlab/Simulink R2007a (version 7.4.0.207).